Numerical simulation of liquid metals in differentially heated enclosure undergoing orthogonal rotation - Baig, M.F.; Zunaid, M. (International journal of heat and mass transfer, 2006)
In this work a numerical investigation has been performed to examine the characteristics of mixed convective heat transfer in square enclosures undergoing orthogonal rotation i.e. rotation axis and gravity axis are orthogonal to each other. A semi implicit finite difference code on a collocated grid is used to solve the momentum and energy equations subject to Boussinesq approximation. The study is carried out for a wide range of operating parameters such as Rayleigh number ( Ra), Taylor number ( Ta), Rotational Rayleigh number ( Ra w) for a fixed Prandtl number ( Pr). The numerical experiments have been carried out for a fixed Pr = 0.01, Ra varies from 10 5 to 10 7 while Ta and Ra w vary from almost 0 to 10 9. Results reveal that significant increase or decrease in heat transfer rates can be achieved by the rotational effects, mainly influenced by centrifugal force.